Discovery and Functional Characterization of Diverse Class 2 CRISPR-Cas Systems - Shmakov, S.; Abudayyeh, O.O.; Makarova, K.S.; Wolf, Y.I.; Gootenberg, J.S.; Semenova, E.; Minakhin, L.; Minakhin, L.; Konermann, S.; Severinov, K.; Zhang, F.; Koonin, E.V.
Microbial CRISPR-Cas systems are divided into Class 1, with multisubunit effector complexes, and Class 2, with single protein effectors. Currently, only two Class 2 effectors, Cas9 and Cpf1, are known. We describe here three distinct Class 2 CRISPR-Cas systems. The effectors of two of the identified systems, C2c1 and C2c3, contain RuvC-like endonuclease domains distantly related to Cpf1. The third system, C2c2, contains an effector with two predicted HEPN RNase domains. Whereas production of mature CRISPR RNA (crRNA)by C2c1 depends on tracrRNA, C2c2 crRNA maturation is tracrRNA independent. We found that C2c1 systems can mediate DNA interference in a 5'-PAM-dependent fashion analogous to Cpf1. However, unlike Cpf1, which is a single-RNA-guided nuclease, C2c1 depends on both crRNA and tracrRNA for DNA cleavage. Finally, comparative analysis indicates that Class 2 CRISPR-Cas systems evolved on multiple occasions through recombination of Class 1 adaptation modules with effector proteins acquired from distinct mobile elements.
Keywords: CASPASE 9; CPF1 PROTEIN; CRISPR ASSOCIATED PROTEIN; ENDONUCLEASE; RIBONUCLEASE; RNA; UNCLASSIFIED DRUG